STRATEGI LAYANAN BIMBINGAN KLASIKAL BLENDED LEARNING BERBASIS PROJECT BASED LEARNING UNTUK MENINGKATKAN SELF REGULATED LEARNING SISWA - Indah Pratiwi Heriyanti; Caraka Putra Bhakti (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2022)
The purpose of this study is to provide an overview and alternative strategies that can be used by counselors or guidance and counseling services in providing independent learning. Learning is a basic obligation and need for all students. Many phenomena that describe students do not know the learning process in themselves. Because there is no self-regulation in the learning process. Self-regulated learning is the ability of students to regulate and manage the learning process such as planning, monitoring, participating, and actively participating in learning. In fact, many students have low self-regulated learning. So it needs the efforts of guidance and counseling teachers to provide services regarding independent learning. Classical guidance services provide facilities and infrastructure to create an independent learning environment. However, classical guidance services are still less effective due to lack of creativity and innovation. So we need an alternative learning that is blended learning. Blended learning is a combination of traditional learning with face-to-face learning. to increase self-regulated learning, it is necessary to learn that causes active participation from students. Project-Based Learning is learning that is carried out in project activities. Based on many studies, project-based learning can improve self-learning ability. So it is hoped that guidance and counseling can provide creative and innovative guidance and counseling services to improve independent learning.